STARD3: A Swiss Army Knife for Intracellular Cholesterol Transport. (June 2019) - Voilquin, Laetitia; Lodi, Massimo; Di Mattia, Thomas; Chenard, Marie-Pierre; Mathelin, Carole; Alpy, Fabien; Tomasetto, Catherine
Intracellular cholesterol transport is a complex process involving specific carrier proteins. Cholesterol-binding proteins, such as the lipid transfer protein steroidogenic acute regulatory-related lipid transfer domain-3 (STARD3), are implicated in cholesterol movements between organelles. Indeed, STARD3 modulates intracellular cholesterol allocation by reducing it from the plasma membrane and favoring its passage from the endoplasmic reticulum (ER) to endosomes, where the protein is localized. STARD3 interacts with ER-anchored partners, notably vesicle-associated membrane protein-associated proteins (VAP-A and VAP-B) and motile sperm domain-containing 2 (MOSPD2), to create ER–endosome membrane contacts. Mechanistic studies showed that at ER–endosome contacts, STARD3 and VAP proteins build a molecular machine able to rapidly transfer cholesterol. This review presents the current knowledge on the molecular and cellular function of STARD3 in intracellular cholesterol traffic.